Структура 180-градусної доменної стiнки поблизу поверхнi ферроiкiв - Eliseev, E. A. (Publishing house "Academperiodika", 2019)
We consider the influence of a built-in surface field on the 180-degree domain wall profile in primary ferroics within the Landau–Ginsburg–Devonshire phenomenological approach. The built-in surface field can be caused by various physical mechanisms for ferroelastic, ferroelectric, and antiferromagnetic media. For instance, it can be a component of the intrinsic surface stress tensor for ferroelastics with order parameter as a component of the strain tensor. We predict the effect of domain wall bending near the surface caused by the built-in field and derived the corresponding approximate analytical expressions.